Occupational health and safety in corporate social responsibility reports - Marileena Koskela (Science Direct, 2022)
There is a current lack of research on occupational health and safety (OH&S) reporting as a part of corporate social responsibility (CSR) reports. The aim of this paper is to analyse the OH&S reporting in (CSR) reports. Five years of CSR reports from three companies representing different business sectors are here used as research material. The results show the OH&S reporting to consist of reporting on occupational health, occupational safety and well-being at work. The companies report mainly about occupational safety with a variety of subareas, whereas the reporting of well-being at work is more seldom and with less variation of subareas. In each theme, the companies report both the results that their OH&S work has yielded and the processes behind these results. As the results show more similarities in OH&S reporting than differences between the companies, more research on OH&S reporting is encouraged.